Hukum Islam dan Perubahan Sosial - Fathullah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2016)
In early period of Islam, a scope of syar’iah is same with a scape of fiqh, that wreat all of doctrine of Islam. Than because of the development of science, both of them are limited by the scope. Syar’iah is means as a role of Allah which has the absolute, everlasting, pure and sacred, so it can not change and it can change by Allah (Syar’i) him self. Whereas, fiqh includes category of science, and as a science, fiqh is the product of human perception (human product), because of it, it has relative and profane, that formula has been influence much by the condition of place and time. In the course of history in early period of fiqh is as a science, than it becomes a dogma. Finally, the fiqh thought which is in early period of Islam is very dynamis and many kinds of development is suitable with the development of society has changed as a dogma which must be memorize, hold it out, and follow as it. Fiqh is the product of the human perception which has dynamis, relative and profane; it has changed to syar’iyah which has absolute, everlasting, pure, and sacred. So, the product of human creation is in a line with god’s sentence. The method and result of fiqh often describes as god’s power, so it impressed as righteousness note of paradise. Even thought truly interpretasion it obey to worldview of expert law (fuqaha), but it often announces as the god’s command.